If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 6 = 7y + 9 Reorder the terms: 6 + -6y = 7y + 9 Reorder the terms: 6 + -6y = 9 + 7y Solving 6 + -6y = 9 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 6 + -6y + -7y = 9 + 7y + -7y Combine like terms: -6y + -7y = -13y 6 + -13y = 9 + 7y + -7y Combine like terms: 7y + -7y = 0 6 + -13y = 9 + 0 6 + -13y = 9 Add '-6' to each side of the equation. 6 + -6 + -13y = 9 + -6 Combine like terms: 6 + -6 = 0 0 + -13y = 9 + -6 -13y = 9 + -6 Combine like terms: 9 + -6 = 3 -13y = 3 Divide each side by '-13'. y = -0.2307692308 Simplifying y = -0.2307692308
| 2(x+4)=-5+1 | | -70+2x=-4x+32 | | 100-(x+2)=x/2 | | 75=-3(-6n-5) | | 256x^2-225= | | -3(x+2)+4(3x-8)=2(4x+7)+2(3x-6) | | -55-12x=-5x+36 | | (4x+9)(x-7)= | | 2(x+4)=-5x | | 2x+4=-5x+1 | | 49n^2-81=0 | | 100=(x+2)+(x/2) | | -28=92+10x | | 100=x+2+x/2 | | 2(2w+12)=68 | | 4x-2(-1x-11)=64 | | 25a^2-80a+64=0 | | Z^2+8=4 | | a+(37+a)+(2a-40)=433 | | s-32=-29 | | 2x+8=352 | | (x)(x+1)(x+2)=36 | | 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) |